A mixed methods assessment of knowledge, attitudes and practices related to aflatoxin contamination and exposure among caregivers of children under 5 years in western Kenya - Abigael O Awuor; Gati Wambura; Isaac Ngere; Elizabeth Hunsperger; Clayton Onyango; Godfrey Bigogo; Lauren S Blum; Peninah Munyua; M Kariuki Njenga; Marc-Alain Widdowson (Cambridge University Press, 2023)
Abstract Objective: Identifying factors that may influence aflatoxin exposure in children under 5 years of age living in farming households in western Kenya. Design: We used a mixed methods design. The quantitative component entailed serial cross-sectional interviews in 250 farming households to examine crop processing and conservation practices, household food storage and consumption and local understandings of aflatoxins. Qualitative data collection included focus group discussions (N 7) and key informant interviews (N 13) to explore explanations of harvesting and post-harvesting techniques and perceptions of crop spoilage. Setting: The study was carried out in Asembo, a rural community where high rates of child stunting exist. Participants: A total of 250 female primary caregivers of children under 5 years of age and thirteen experts in farming and food management participated. Results: Study results showed that from a young age, children routinely ate maize-based dishes. Economic constraints and changing environmental patterns guided the application of sub-optimal crop practices involving early harvest, poor drying, mixing spoiled with good cereals and storing cereals in polypropylene bags in confined quarters occupied by humans and livestock and raising risks of aflatoxin contamination. Most (80 %) smallholder farmers were unaware of aflatoxins and their harmful economic and health consequences. Conclusions: Young children living in subsistence farming households may be at risk of exposure to aflatoxins and consequent ill health and stunting. Sustained efforts to increase awareness of the risks of aflatoxins and control measures among subsistence farmers could help to mitigate practices that raise exposure.